Who was Marie Curie? - Stine, Megan; Illustrated by Hammond, Ted (New York Penguin Workshop, 2014)
Born in Warsaw, Poland on November 7, 1867, Marie Curie was forbidden to attend the male-only University of Warsaw, so she enrolled at the Sorbonne in Paris to study physics and mathematics. There she met a professor named Pierre Curie, and the two soon married, forming one of the most famous scientific partnerships in history. Together they discovered two elements and won a Nobel Prize in 1903. (Marie later won another Nobel for chemistry in 1911.) She died in Savoy, France, on July 4, 1934, a victim of many years of exposure to toxic radiation.
Include Illustration and Bibliography
Keywords: France -- Women chemists -- Radioactivity